Dropout rates and reasons for dropout among patients receiving clozapine - Sandeep Grover; Eepsita Mishra; Subho Chakrabarti (Indian Journal of Psychiatry)
Background and Aim: The present study aimed to assess the treatment dropout rates, reasons for treatment dropout, and clozapine discontinuation rate among patients attending a tertiary care center in North India. Materials and Methods: Clozapine data bank was used to identify patients on clozapine, and their treatment records were reviewed for the period Jan 2020–March 2020. Patients who did not follow-up at least once in the last 6 months were considered to have dropped out and were contacted telephonically to understand the reasons for dropout. Treatment records of those following up regularly were reviewed to check if clozapine was discontinued and if so, the reason for the same was evaluated. Results: Out of 671 patients on clozapine, 495 (73.8%) were still on regular follow-up and the remaining 176 (26.2%) had dropped out of treatment. Out of the 176 patients who had dropped out of treatment, 84 could be contacted. Common reasons for dropout were long distance from the hospital (n = 27), long waiting time for consultation (n = 8), no benefit with treatment (n = 17), side effects with medication (n = 10), moving away to another place (n = 6), refusal by the patient to follow-up (n = 7), patient improved and so did not feel the need to continue treatment (n = 7), and other reasons (n = 37). Conclusion: About one-fourth of patients who had started treatment with clozapine dropped out from the treatment. The most common reasons for dropout from treatment included long distance from the hospital and no benefit from treatment.